Current research on fungi in chronic wounds - Ge, Yumei; Wang, Qingqing (Frontiers in Molecular Biosciences, 2023)
The occurrence of chronic wounds is a major global health issue. These wounds are difficult to heal as a result of disordered healing mechanisms. The most common types of chronic wounds are diabetic ulcers, pressure ulcers, arterial/venous ulcers and nonhealing surgical wounds. Although bacteria are an important cause of chronic nonhealing wounds, fungi also play a substantial role in them. The fungal infection rate varies with different chronic wound types, but overall, the prevalence of fungi is extremely underestimated in the clinical treatment and management of chronic wounds. Wounds and ulcers can be colonized by host cutaneous, commensal or environmental fungi and evolve into local infections, causing fungemia as well as invasive fungal disease. Furthermore, the fungi involved in nonhealing wound-related infections help commensal bacteria resist antibiotics and the host immune response, forcing wounds to become reservoirs for multiresistant species, which are considered a potential key factor in the microbial bioburden of wounds and ulcers. Fungi can be recalcitrant to the healing process. Biofilm establishment is the predominant mechanism of fungal resistance or tolerance to antimicrobials in chronic nonhealing wounds. Candida albicans yeast and Trichophyton rubrum filamentous fungi are the main fungi involved in chronic wound infection. Fungal species diversity and drug resistance phenotypes in different chronic nonhealing wound types will be emphasized. In this review, we outline the latest research on fungi in chronic wounds and discuss challenges and future perspectives related to diagnosing and managing chronic wounds.